IMPLEMENTASI KEBIJAKAN PERLINDUNGAN HUTAN DI INDONESIA - Suyono Makruf; Iqbal Miftakhul Mujtahid; Pardamean Daulay (Journal Publicuho, 2023)
This research examines the implementation of forest protection policies in North Konawe Regency, Southeast Sulawesi Province, by the Gakkum LHK Kendari Post, with the aim of making a significant contribution to the broader improvement of forest policy implementation in Indonesia. The study involves an analysis of implementation effectiveness, factors influencing implementation, and policy characteristics as well as environmental issues. The research employs a qualitative research method, detailing findings through interviews, observations, and document analysis. The results indicate personnel imbalance, budget limitations, deforestation due to illegal mining, and challenges in infrastructure and coordination as the primary obstacles to policy implementation. Applying Mazmanian and Sabatier's policy implementation theory provides insights into the crucial roles of environmental factors, policy characteristics, and issue specifics in achieving successful forest protection policy implementation.